Role of Mitomycin C in Management of Anterior Urethral Stricture - Muhammad Umar Habib, Muhammad Rameez, Jamshed Rahim, Amna Kazi, Jamil Rahim, Malik Zain Ahmed (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Urethral stricture disease can result from any of the following causes inflammatory, ischemic or traumatic processes. Many risk factors of urethral stricture disorder have been documented. Urethral stricture disorder is a disease of antiquity. Recurrence of the stricture is the most common adverse outcome of surgery. Objective: To compare the clinical recurrence rate in urethral stricture after direct vision internal optical urethrotomy followed by intralesional injection of mitomycin C inoculation and internal optical urethrotomy alone. Study Design: Randomized control trial Place and Duration of Study: Department of Urology, Jinnah Hospital, Lahore from 1st July 2019 to 31st January 2021. Methodology: Eighty patients were enrolled and they were divided into two groups; group A and group B. Group A was treated with intralesional mitomycin C and group B with internal optical urethrotomy alone. The patients were followed up for 6 months and clinical outcome and recurrence were noted. Results: The patients’ average age was 47.91+16.19 years. About 65 (81.25%) strictures reported were caused by iatrogenic and 15(18.75%) strictures caused by infection. The recurrence of weak urinary stream occurred in 28 patients and it was found significantly higher in control group 21(52.5%) as compared to group given mitomycin C 7 (17.5%) Conclusion: Both intralesional mitomycin C inoculation and internal optical urethrotomy has better outcome than internal optical urethrotomy alone. Keywords: Intralesional mitomycin C, Urethral stricture, Urethrotomy.